The Remarkable Anti-Breast Cancer Efficacy and Anti-Metastasis by Multifunctional Nanoparticles Co-Loading Squamocin, R848 and IR 780 - Wang X; Liu X; Guo Y; Gong T; Lu W; Han M; Guo Y; Wang X (International Journal of Nanomedicine, 2024)
Xi Wang,1 Xinxin Liu,1 Yaoyao Guo,1,2 Tingting Gong,1 Wenmin Lu,1,3 Meihua Han,1 Yifei Guo,1 Xiangtao Wang1 1Institute of Medicinal Plant Development, Chinese Academy of Medical Sciences and Peking Union Medical College, Beijing, People’s Republic of China; 2College of Traditional Chinese Medicine, Shenyang Pharmaceutical University, Shenyang, Liaoning Province, People’s Republic of China; 3College of Pharmacy, Heilongjiang University of Chinese Medicine, Harbin, Heilongjiang Province, People’s Republic of ChinaCorrespondence: Xiangtao Wang, Institute of Medicinal Plant Development, Chinese Academy of Medical Sciences and Peking Union Medical College, No. 151, Malianwa North Road, Haidian District, Beijing, 100193, People’s Republic of China, Tel +86-10-57833266, Email xtaowang@163.comBackground: Breast cancer is a heterogeneous disease globally accounting for approximately 1 million new cases annually. Chemotherapy remains the main therapeutic option, but the antitumor efficacy needs to be improved.Methods: Two multifunctional nanoparticles were developed in this paper using oleic acid and mPEG2k-PCL2k as the drug carriers. Squamocin (Squ) was employed as a chemotherapeutic agent. Resiquimod (R848) or ginsenoside Rh2 was co-encapsulated in the nanoparticles to remold the immunosuppressive tumor microenvironment, and IR780 was coloaded as a photosensitizer to realize photothermal therapy.Results: The obtained Squ-R848-IR780 nanoparticles and Squ-Rh2-IR780 nanoparticles were uniformly spherical and approximately (162.200 ± 2.800) nm and (157.300 ± 1.1590) nm, respectively, in average diameter, with good encapsulation efficiency (above 85% for each drug), excellent stability in various physiological media and high photothermal conversion efficiency (24.10% and 22.58%, respectively). After intravenous administration, both nanoparticles quickly accumulated in the tumor and effectively enhanced the local temperature of the tumor to over 45 °C when irradiated by an 808 nm laser. At a low dose of 0.1 mg/kg, Squ nanoparticles treatment alone displayed a tumor inhibition rate of 55.28%, pulmonary metastasis inhibition rate of 59.47% and a mean survival time of 38 days, which were all higher than those of PTX injection (8 mg/kg) (43.64%, 25 days and 37.25%), indicating that Squ was a potent and effective antitumor agent. Both multifunctional nanoparticles, Squ-Rh2-IR780 nanoparticles and Squ-R848-IR780 nanoparticles, demonstrated even better therapeutic efficacy, with tumor inhibition rates of 90.02% and 97.28%, pulmonary metastasis inhibition rates of 95.42% and 98.09, and mean survival times of 46 days and 52 days, respectively.Conclusion: The multifunctional nanoparticles coloaded with squamocin, R848 and IR 780 achieved extraordinary therapeutic efficacy and excellent antimetastasis activity and are thus promising in the future treatment of breast tumors and probably other tumors.Keywords: breast cancer, multifunctional nanoparticle, antitumor efficacy, antimetastasis, combined therapy